Software and Data Technologies 5th International Conference, ICSOFT 2010, Athens, Greece, July 22-24, 2010. Revised Selected Papers - Cordeiro, José; Virvou, Maria; Shishkov, Boris (Communications in Computer and Information Science,, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Conference on Software and Data Technologies, ICSOFT 2010, held in Athens, Greece, in July 2010. The 30 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from a total of 410 submissions in two rounds of reviewing and improvement. The papers cover a wide range of topics and are organized in four general topical sections on healthinf, biodevices, biosignals, and bioinformatics.